2008
DOI: 10.2214/ajr.07.2537
|View full text |Cite
|
Sign up to set email alerts
|

Combined Percutaneous Radiofrequency Ablation and Ethanol Injection for Hepatocellular Carcinoma in High-Risk Locations

Abstract: The combination of radiofrequency ablation and PEI in the management of HCC in high-risk locations has a slightly higher primary effectiveness rate than does radiofrequency ablation alone. A randomized controlled study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 30 publications
2
91
2
Order By: Relevance
“…32,33 In these studies, the principal role of ethanol was to induce a larger necrotic area and to minimize complications. 34,35 To our knowledge, the present study is the first to examine the efficacy of the combination of these 2 modalities in treating predominantly cystic thyroid nodules. The present study has several limitations.…”
Section: Initialmentioning
confidence: 95%
“…32,33 In these studies, the principal role of ethanol was to induce a larger necrotic area and to minimize complications. 34,35 To our knowledge, the present study is the first to examine the efficacy of the combination of these 2 modalities in treating predominantly cystic thyroid nodules. The present study has several limitations.…”
Section: Initialmentioning
confidence: 95%
“…Incomplete ablation of tumours after the local treatment is independently associated with tumour progression [21,22]. Our results showed that, despite using lower RF power, the complete ablation and primary effectiveness of index tumours was achieved similarly between both groups.…”
Section: T C Macatula C-c Lin C-j Lin Et Almentioning
confidence: 51%
“…In the case of RF ablation, these treatments include, in addition to liposome-encapsulated doxorubicin therapy, treatments with intravenous liposomal cisplatin ( 18 ), liposomal 5-fl uorouracil ( 18 ), arsenic trioxide ( 20 ), and hydralazine ( 24 ); intravenous and intratumoral Pluronic block copolymers ( 28 ); intratumoral ethanol ( 11,39 ) and unencapsulated doxorubicin ( 12 ); intraperitoneal arsenic trioxide ( 20 ); interstitially implanted 5-fl uorouracil-laden polymer rods ( 27 ); oral sorafenib ( 21 ); and transarterial chemoembolization ( 19,23 ). In human trials, the benefi ts of combined RF ablation-intratumoral ethanol therapy ( 30,40,41 ) and combined RF ablation-transarterial chemoembolization ( 15,22,25,29,31,42 ) have been shown. The synergistic effect of combined RF ablation-chemotherapy has been best established with intravenous liposomal doxorubicin.…”
Section: Discussionmentioning
confidence: 99%